2010
DOI: 10.4028/www.scientific.net/kem.442.15
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zr Addition on the Mechanical Behavior, Ductility and Wear Resistance of Aluminum Grain Refined by Titanium

Abstract: Aluminum and its alloys are the second most commonly used metal for a variety of engineering applications. They solidify in columnar structure with large grain size which normally affects their mechanical behavior and surface quality. It is now becoming customary in aluminum foundry to grain refine their structure by adding either titanium or titanium + boron to their melt before solidification. In this paper, the effect of addition of Ti on the mechanical properties, ductility and wear resistance of commercia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…However, when Zr is added In the presence of Ti+B resulted in enhancing the grain refining efficiency of Ti+B. which agrees with the previous findings of researchers, [11,12,13,16]. The maximum decrease in the case of adding both Ti+B and Zr together is 53.2% compared to 33% decrease in the case of Ti+B addition.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…However, when Zr is added In the presence of Ti+B resulted in enhancing the grain refining efficiency of Ti+B. which agrees with the previous findings of researchers, [11,12,13,16]. The maximum decrease in the case of adding both Ti+B and Zr together is 53.2% compared to 33% decrease in the case of Ti+B addition.…”
Section: Resultssupporting
confidence: 90%
“…Mass to mass the ternary AT5B1 alloy is 5 to 6 times more efficient than binary AT6 (Al-6%Ti) alloy although boron itself is not a grain refiner. The literature on grain refinement of aluminum and its alloys is voluminous, however most of the work is directed on the metallurgical aspects [1,2,3,4,5,6,7,8,9,10,11] and little is directed towards the mechanical behavior, [12,13,14,15] and hardly any work is reported on the effect of addition of these grain refiners on the formability. Detailed review on the grain refinement of Al and its alloys is given by Zaid [16].…”
Section: Introductionmentioning
confidence: 99%
“…Titanium and titanium + boron are the most widely used as effective refiners. The literature on the subject is voluminus from the metallurgical and mechanical aspects [17][18][19][20][21][22][23][24]. Review of this literature is given by the first author in reference [17].In this section, the effect of the grain refinement on the grain size, hardness, fatigue failure and fracture surface of the commercially pure aluminum is presented and discussed.…”
Section: Peening Intensity and Saturationmentioning
confidence: 99%
“…This has engaged many researchers in the last six decades, when it was found that the presence of Ti in Al resulted in grain refinement of its structure from large columnar structure with large grain size into equi-axed refined structure with small grains which caused enhancement in its mechanical behavior and surface quality, [6][7]. The literature on grain refinement of Al and its alloys and zinc aluminum alloys is voluminous, [8][9][10][11][12][13][14][15]. Review of the grain refinement of Al and its alloys and zinc-aluminum alloys are given and discussed [8] and [9][10] respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The literature on grain refinement of Al and its alloys and zinc aluminum alloys is voluminous, [8][9][10][11][12][13][14][15]. Review of the grain refinement of Al and its alloys and zinc-aluminum alloys are given and discussed [8] and [9][10] respectively. Another method of grain refinement beside the refinement by some rare earth elements is the severe plastic deformation, SPD, processes, which have engaged some researchers in the last two decades many studies have been directed towards material processing by applying severe plastic deformation, referred to later as SPD.…”
Section: Introductionmentioning
confidence: 99%